High - tech - textiles in competition sports - Nusser, M.; Senner, V. (Procedia Engineering, 2010)
The discrepancy of performance among competitive athletes is getting smaller and smaller. Therefore wearing high tech textile could help to get advantage over competitors. For this reason a lot of investigation has been done on developing high tech textiles that support the athletes to better performance. The aims of this study were to give an overview on the available products and to evaluate their level of innovation. Furthermore the research project should reveal which products are effectively used in trainings and competition. Finally the study elicits the status of current research and shows prospective research potential.